Public enterprise and privatization in a new century: evolving patterns of governance and public management - Wettenhall, Roger; Thynne, Ian (2002)
This article serves to introduce the symposium in three interrelated ways. It begins by noting the genesis of the project and acknowledging the need for caution in making predictions. It then addresses several issues and concerns of historical, contemporary, and likely future significance to public enterprise and privatization. These include the advent and implications of new public management (NPM), the extent to which privatization by way of disinvestment has won public acceptance, the emerging modes and styles of governance, and the changing role and capacity of the modern state. It ends by highlighting the thrust of the discussions in the next five articles which provide relevant perspectives of national, regional and global importance. - Reproduced.
Keywords: Good governance; Privatization; Public administration